Recycled aggregate concrete: Localized failure assessment in thermodynamically consistent non-local plasticity framework. (1st January 2017) - Ripani, Marianela; Etse, Guillermo; Vrech, Sonia
Highlights: A thermodynamically consistent gradient theory for recycled aggregate concretes is proposed. This constitutive model depends on the confinement pressure and the recycled aggregate contents. The occurrence of localized failure is studied by means of the acoustic tensor. The performance of the acoustic tensor is analyzed taking into account different recycled aggregate contents. Abstract: A gradient plasticity theory is extended to predict the mechanical failure behavior of concrete with recycled aggregates. A relevant feature of the novel constitutive formulation is its full consistency with the thermodynamic laws regarding hardening and softening response behaviors. The proposed model includes a formulation of a maximum strength surface which is dependent on the recycled aggregate content. While the hardening law is formulated in the framework of classical-local elastoplasticity, the post-peak behavior is described by means of a non-local gradient and fracture-energy-based law. Thereby, the gradient and fracture-energy characteristic lengths are described in terms of the acting confining pressure and the recycled aggregate content. The formulation of the proposed constitutive theory is complemented by the description of the associated localization indicator, based on the acoustic or localization tensor. Finally, numerical results are presented to demonstrate the predictive capabilities of the proposed model and the performance of the localization indicator for different critical stresses and recycled aggregate contents.